What extraneous solution arises when the question √(x+3)=2x is solved for x by first squaring both sides of the equation?

When we square both sides we get: x + 3 = 4x^2

To solve, we need it equal to zero: 4x^2 - x - 3 = 0

Factoring we get: (4x + 3)(x - 1) = 0

This gives us x = -3/4 and x = 1

The x = 1 is a fine answer when we plug it back in. However, the -3/4 doesn't work. It is therefore, extranious.

Hope that helps.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up